Plan de fortalecimiento ante ataques informáticos del Hospital de Especialidades Portoviejo basados en sistemas de correlación de Log - Mora Cruzatty, Andy Alcides (2022)
The technological infrastructures represent for the current institutions an asset of extreme importance in order to manipulate and manage the information, in this sense El Hospital de Especialidades Portoviejo, has a significant quantity and variety of technological instruments for the support of its daily activities, likewise this institution does not have a centralized tool for monitoring and preventing computer attacks. The objective of this research was the elaboration of an improvement plan to prevent and repeal computer attacks of the Hospital de Especialidades Portoviejo based on log correlation systems. The methodology used in the research was PPDIOO which includes the phases of: Preparation, Planning, Design, Implementation, Operation and Optimization, applied to the Security Information and Event Management (SIEM) event correlation systems using the AlienVault OSSIM system, which allows comparing, integrating and visualizing security incidents in real time, allowing the implementation of a depth strategy for defense. As a result of the investigation, an improvement plan was established to strengthen the current infrastructure of the Hospital de Especialidades Portoviejo against computer attacks, the conclusion of the research noticed that: the use of the OSSIM tool made it possible to improve cybersecurity mechanisms guaranteeing security, integrity and availability, thus avoiding anomalies in the network and failures in its services, combined with different integrated monitoring and detection tools, allowing for centralized security management within the Institution.